The Firm Size Distribution across Countries and Skill-Biased Change in Entrepreneurial Technology - Markus Poschke (Institute for the Study of Labor (IZA), 2014)
How and why does the firm size distribution differ across countries? Using two datasets covering more than 30 countries, this paper documents that several features of the firm size distribution are strongly associated with income per capita: the entrepreneurship rate and the fraction of small firms fall with per capita income across countries, while average firm employment, the median and higher percentiles of the firm size distribution, and the dispersion and skewness of employment all rise with per capita income. The paper broadens existing evidence on the first three facts to cover more countries and newly introduces the last three to the literature. It then proposes a simple theory of skill-biased change in entrepreneurial technology motivated by recent microeconomic literature that fits with the evidence. For this, it introduces two additional features into an otherwise standard occupational choice, heterogeneous firm model a la Lucas (1978): technological change does not benefit all potential entrepreneurs equally, and there is a positive relationship between an individual's potential payoffs in working and in entrepreneurship. If some firms consistently benefit more from technological progress than others, they stay closer to the frontier, while others fall behind. Because wages rise for all workers, marginal entrepreneurs exit and become workers. Quantitatively, the model fits both the U.S. time series experience and cross-country patterns well.
Keywords: E24; J24; L11; L26; O30; 330; occupational choice; entrepreneurship; firm size; skill-biased technical change